Developing Urban Design Guidelines for Creating Sustainable Healthy Neighbourhoods - Raj, Aparna B; Kini, Manoj; Roshini, K V (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2024)
The research focuses on community engagement and environmentally friendly methods in the creation of healthy neighbourhoods. Public health issues, environmental degradation, and social inequality are on the rise in urban areas as a result of rapid urbanization. A possible solution to these problems is a growing understanding of the role that good urban design can play in improving people’s health and happiness. In order to identify important ideas and strategies for making healthy built environments, this study examines case studies of successful healthy communities from all over the globe, such as Medellin, Colombia; Vauban, Freiburg, Germany; and Copenhagen, Denmark, among others. In order to build healthier, more sustainable communities, the research presents a set of thorough recommendations based on public health research, stakeholder participation, and urban design ideas. In order to promote social inclusion, preservation of the environment, and equal access to resources, the standards include a wide range of topics related to urban planning, such as connectivity, the supply of green space, mixed land use, and community participation. By drawing from a variety of research fields, this research builds to what is already known about healthy neighbourhoods, vibrant neighbourhoods that all individuals can be a part of.